Clinical presentation and outcome prediction of clinical, serological, and histopathological classification schemes in ANCA-associated vasculitis with renal involvement. Issue 7 (July 2016) - Córdova-Sánchez, Bertha; Mejía-Vilet, Juan; Morales-Buenrostro, Luis; Loyola-Rodríguez, Georgina; Uribe-Uribe, Norma; Correa-Rotter, Ricardo
Abstract Several classification schemes have been developed for anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), with actual debate focusing on their clinical and prognostic performance. Sixty-two patients with renal biopsy-proven AAV from a single center in Mexico City diagnosed between 2004 and 2013 were analyzed and classified under clinical (granulomatosis with polyangiitis [GPA], microscopic polyangiitis [MPA], renal limited vasculitis [RLV]), serological (proteinase 3 anti-neutrophil cytoplasmic antibodies [PR3-ANCA], myeloperoxidase anti-neutrophil cytoplasmic antibodies [MPO-ANCA], ANCA negative), and histopathological (focal, crescenteric, mixed-type, sclerosing) categories. Clinical presentation parameters were compared at baseline between classification groups, and the predictive value of different classification categories for disease and renal remission, relapse, renal, and patient survival was analyzed. Serological classification predicted relapse rate (PR3-ANCA hazard ratio for relapse 2.93, 1.20–7.17, p  = 0.019). There were no differences in disease or renal remission, renal, or patient survival between clinical and serological categories. Histopathological classification predicted response to therapy, with a poorer renal remission rate for sclerosing group and those with less than 25 % normal glomeruli; in addition, it adequately delimited 24-month glomerular filtration rate (eGFR) evolution, but it did not predict renal nor patient survival. On multivariate models, renal replacement therapy (RRT) requirement (HR 8.07, CI 1.75–37.4, p  = 0.008) and proteinuria (HR 1.49, CI 1.03–2.14, p  = 0.034) at presentation predicted renal survival, while age (HR 1.10, CI 1.01–1.21, p  = 0.041) and infective events during the induction phase (HR 4.72, 1.01–22.1, p  = 0.049) negatively influenced patient survival. At present, ANCA-based serological classification may predict AAV relapses, but neither clinical nor serological categories predict renal or patient survival. Age, renal function and proteinuria at presentation, histopathology, and infectious complications constitute the main outcome predictors and should be considered for individualized management.